Microbial Biodiversity in Sediment from the Amuyo Ponds: Three Andean Hydrothermal Lagoons in Northern Chile - Claudia Vilo; Francisca Fábrega; Víctor L. Campos; Benito Gómez-Silva (Microorganisms)
The Amuyo Ponds (APs) are a group of three brackish hydrothermal lagoons located at 3700 m above sea level in a pre-Andean setting in the Atacama Desert. Each pond shows a conspicuous green (GP), red (RP), or yellow (YP) coloration, and discharges water rich in arsenic and boron into the Caritaya River (Camarones Basin, northern Chile). Microorganisms are subjected to harsh environmental conditions in these ponds, and the microbial composition and diversity in the Amuyo Ponds’ sediments are unknown. The microbial life colonizing AP sediments was explored by metagenomics analyses, showing a diverse microbial life dominated by members of the bacterial domain, with nearly 800 bacterial genome sequences, and sequences associated with Archaea, Eukarya, and viruses. The genus Pseudomonas was more abundant in GP and YP sediments, while the genera Pseudomonas, Aeromonas, and Shewanella were enriched in RP sediments. Archaeal composition was similar in all sediments, and enriched with methanogens sequences from the Archaeoglobi and Halobacteria classes. Abundant fungi sequences were detected in all sediments from the phyla Blastocladiomycota and Ascomycota. We also report putative functional capabilities related to virulence and defense genes, the biosynthesis of secondary metabolites, and tolerance to arsenic. Thirteen bacterial and fourteen viral metagenome-assembled genomes were reconstructed and informed here. This work expands our knowledge on the richness of the microorganisms in the APs and open further studies on the ecology and genomics of this striking Andean geosite.